QUALIDADE DE VIDA EM MULHERES TRATADAS POR CÂNCER DE MAMA EM SÃO LUÍS-MA - Bezerra, Karla Barros (2012)
The effects of the treatment of breast cancer on the quality of life have been widely discussed in the literature. However, little is known about the subject in northeastern Brazil. The purposewasto evaluatethequality of life of patients treated for breast cancer in Sao Luis, MA. We conducted a cross-sectional study with 197 women Who underwent breast surgery and were attended in a Oncology Reference Hospital in Maranhao. The study included women treated unilaterally, regardless of adjuvant therapy conducted or in progress, no other malignancy. The sociodemographic variables studied were: age, education, marital status, ethnicity and number of children. Variables related to treatment were type of surgery, time since surgery and neo-adjuvant and adjuvant therapy. Quality of life was assessed using the FACT-B, applied in one step by a team of trained researchers. The variables were presented as Mean and Standard Deviation. For the classification groups with more than three classes, we used the ANOVA orKruskal Wallis. For those with only two classes, we applied Student's t test when there was a normal distribution or Mann-Whitney test for nonparametric variables. To check the correlation between them and the scores of the domains, we applied the Pearson linear correlation test. The significance level adopted for all tests was α less than or equal to 0,05.Withanaverage age of 53.02 years (SD ± 11,71), white (44,67%), school (46,19%), married or in consensual union (57,87%) and average of 3,17 children (SD±2,73), women underwent mastectomy (63,46%) or breast conserving surgery (36,54 %), less than 6 years of surgery (92,90%). Neo-adjuvant therapies were not adopted in the majority (86,30%), but 92,38% received adjuvant therapies. The average values through the FACT-B showed a tendency to good quality of life, and the Functional Domain was the most committed and the total score, the less committed. Age, education, marital status, ethnicity, type and duration of surgery and adjuvant therapies influenced the quality of life in at least one Domain or Score of questionnaire, and the relationships were more marked with the sub-scale breast cancer (p=0,0001) and the FACT-B total score (p=0,0001) and adjuvant therapy with sub-scale breast cancer (p<0,0001). Pearson said there was a positive correlation between Domains and the questionnaire Scores. Qualityoflifewas relatively good, but was negatively influenced by mastectomy, the shortest time since the surgery and adjuvant therapies.